(untitled) (Journal of Hama University, 2026)
The research aimed to determine the level of influence of strategic thinking on digital marketing in its dimensions (attraction, communication, immersion, learning, and retention) among administrative employees in the Local Administration Directorate in Lattakia Governorate. This research used a descriptive and analytical approach. 121 questionnaires were distributed to all administrative employees in the Local Administration Directorate in Lattakia, and all of these questionnaires were subject to statistical analysis. The researcher used SPSS 2020 for statistical analysis. The research results showed that strategic thinking had an impact on digital marketing in its various dimensions, with a percentage of 0.813. The correlation coefficient between strategic thinking and digital marketing reached 0.903, which is a strong correlation coefficient. The coefficient of determination reached 0.813, meaning that 81% of digital marketing changes were attributed to changes in strategic thinking. The results were arranged in descending order as follows: immersion, attraction, learning, retention, and communication